'NAY, 'TAY, BAKLA, TOMBOY Lived Experiences of Filipino Queer Young Adults in Coming Out to their Families - Pineda, Beatrice D. L.; Suguitan, Romina Venezia C.; Francisco, Felicie Nicole D.L. (Quezon City University of the Philippines Diliman, 2024)
Coming out is a unique and significant experience for the queer young adult, made even more so when coming out to the family, who stands as the primary social and support system of the individual. The purpose of this study was to discover how queer young adults come out to their families, and how the family responds in return. Eight Filipino queer young adults aged 18 to 26, living in Quezon City, Philippines, and have come out to their families were interviewed in order to gather data. Through an inductive thematic analysis, identity development, coming out experience, and the responses of the family were discussed. From here, it was revealed that queer young adults undergo a series of stages in developing their sexual and gender identity. They came out to their family in different ways and multiple times, emphasizing that coming out is not a linear nor monolithic experience. The various social and environmental factors that influenced the family’s perspective on the LGBTQ+ community also played a role in their diverse responses to the coming out. Finally, it all circled back to the queer young adult, as the whole coming out experience brought about different outcomes and effects to them. Overall, the coming out experience of queer young adults to their families is diverse and proves to be of significant impact to the wellbeing of the queer young adult. The results of this study will contribute to the ongoing discourse on family dynamics and relationships, especially with queer family members, and the role of the family on the wellbeing of the queer young adult.
In partial fulfillment for the Degree of Bachelor of Science in Family Life and Child Development
Thesis
Keywords: Coming out; Family; Young adult; Queer